STUDY OF RESIDENTIAL SETTLEMENTS TOWARDS SPATIAL IN PASSO REGION, AMBON CITY - W S Pinoa (EDU SCIENCES JOURNAL, 2020)
Passo region is in accordance with the results of observation, many residential buildings are located in protected areas, commensurate with the coast, commensurate with rivers and around the spring, as well as buildings that do not have a building permit. IMB seems easy to obtain without taking into account the City Planning and Spatial Planning. Hence why, the writer cunducting the research with the title â€œStudy of Residential Settlements Towards Spatial in Passo Region, Ambon Cityâ€